Miconia waimiri-atroari (Miconieae, Melastomataceae): a new species from the Brazilian Amazon Forest - Meirelles, Julia; Furlan Sartor, Mariana; Lopes Chagas, Rennan; Caddah, Mayara Krasinski (Phytotaxa, 2021)
Miconia waimiri-atroari is presented here as a new species from the Brazilian Amazon Forest. This new species has discolorous leaf blades, inflorescences with scorpioid branches, and petals and antesepalous stamen connectives with glandular trichomes. It has been misidentified as Miconia argyrophylla, another species from the Amazon Forest that has this same set of characters. However, the new species has cylindrical young branches (vs. quadrangular in M. argyrophylla), stellate trichomes on leaf abaxial surface (vs. arachnoid), stamens with yellow filaments that turn red in old flowers (vs. stamens with white filaments that only turn pale in old flowers), and style with glandular trichomes (vs. glabrous). At the moment, the species is only known from a small area north of Manaus, state of Amazonas, Brazil. Morphological description, illustrations, general comments and comparison to other similar species are also provided.